Investigating acute coin discoloration by solution immersion - Ab.Llah, Muhammad Fakhriy (Pusat Pengajian Kesihatan, 2015)
The third series of the 20 sen and 50 sen coins made of nickel-brass are prone to discolouration after few years of circulation. The discolouration causes tire brass colour golden coins to change greenish in colour. In order to investigate the discoloration, new 20 sen coins were exposed to various environmental conditions to simulate worst case scenario. New coins morphology and weight recorded and then were submerged in containers containing seawater, river water, well water, bleaching agent, fizzy drink (Pepsi, Root beer and Orange Mirinda), 10g NaCl solution, 50g NaCl solution and 100g NaCl solution with a control coin not submerged in any solution and placed in normal room temperature. Daily observations were made in 30 days by using stereomicroscope to identify the pattern of discoloration of each coin. Results indicate that each solution can caused corrosion and produced different pattern discoloration of the coins. It is hoped that a discoloration timeframe is obtained which would be useful for forensic investigations and that the findings would be usefill for future coin design.